Research on Basic Mechanical Properties and Fracture Damage of Coal Gangue Concrete Subjected to Freeze-Thaw Cycles. (14th June 2021) - Huang, Min; Duan, Jingmin; Wang, Jiakai
Abstract : In order to study the freeze-thaw damage law of the basic mechanical properties and fracture performance of coal gangue concrete, four kinds of coal gangue concrete specimens with different replacement rates of coal gangue coarse aggregate were designed, and then, the basic mechanical test and three-point bending loading were carried out under different times of the freeze-thaw cycle. The test results show that the compressive strength and flexural strength of concrete decrease with the increase of coal gangue aggregate content, and the higher the content of coal gangue aggregate is, the greater the freeze-thaw damage of coal gangue concrete is. The coal gangue reduces the fracture resistance of concrete, and the higher the replacement rate of coal gangue coarse aggregate is, the lower the fracture toughness and fracture energy of concrete is. The freeze-thaw cycle causes the obvious decrease of fracture toughness and fracture energy of concrete because the moisture content of coal gangue particles is higher; the freeze-thaw damage of coal gangue concrete is more serious than that of ordinary concrete, and the higher the substitution rate of replacement of coal gangue coarse aggregate is, the higher the freeze-thaw damage of fracture toughness and fracture energy is. The correlation between the freeze-thaw times and the two parameters of fracture toughness and fracture energy damage of coal gangue concrete after freeze-thaw cycles is good. The relationship between the two parameters and the freeze-thaw times can be fitted by power function y = a x b, and the fitted power index value of fracture toughness is higher than that of fracture energy.